Preparation of terpene-derived fungicidal candidates with a 1,3,4-thiadiazole moiety for natural product-inspired agrochemical discovery - Geng, Y.; Gui, K.; Pan, T.; Ye, J.; Li, J.; Feng, J.; Gao, Y.
For the purpose of sufficient potential fungicidal candidate development from natural plant secondary metabolites, a series of terpene-derived compounds containing a 1,3,4-thiadiazole moiety were designed and prepared. The antifungal activity of the target compounds was evaluated by mycelial growth rate inhibition. A systematic and comprehensive evaluation of antifungal activity against Valsa mali indicated that the target compounds exerted relatively satisfactory inhibitory effect, and some compounds showed superior activity to the commercial pesticide boscalid. The notable compound, 3-fluoro-N-(5-(4-isopropylcyclohexa-1,3-dien-1-yl)? 1,3,4-thiadiazol-2-yl)benzenesulfonamide (4a27)showed a satisfactory EC50 value of 3.785 ?g/mL. The conspicuous effect caused by compound 4a27 on the composition and function of the cell membrane and cell wall was confirmed in subsequent studies on the biochemistry and physiology responses of V. mali. In addition, the mycelial morphology, organelles, ergosterol content, and pectinase activity were affected by the test compound. The structure-activity relationship (SAR)studies revealed that the 1,3,4-thiadiazole and sulfoxide scaffold introduction were crucial for activity improvement. Moreover, a satisfactory quantitative structure-activity relationship (QSAR)model with four descriptors (R2 = 0.9035, F = 53.86, s2 = 0.0158)was obtained through linear regression analysis. This systematic study provides inspiration for the rational design of novel antifungal agents with high efficacies.
Keywords: TERPENE; 1,3,4-THIADIAZOLE; ANTIFUNGAL ACTIVITY; BIOCHEMISTRY RESPONSE; PHYSIOLOGY RESPONSE; QSAR